Persepsi Guru terhadap Pembelajaran Berpraktikum dengan Menggunakan Virtual Lab di Saat Pandemi - Rina Hidayati Pratiwi; Endang Sulistyaniningsih; Lengsi Manurung (Universitas Majalengka, 2022)
Practical learning cannot be replaced by relying solely on theory. Even in a pandemic situation. Various virtual lab applications have finally started to appear and are used by most teachers. This study aims to present information related to teachers' perceptions of practical learning using a virtual lab. at various school levels. Information was obtained from interviews and filling out questionnaires to 56 respondents from 4 school levels, namely elementary school, junior high school, high school and tutoring educational institutions. The method used in this research is descriptive qualitative research method. Most of the respondents were dominated by high school teachers (59%). The results of the study showed that 100% of the teachers who were respondents in this study were more comfortable and preferred the practicals that were carried out directly compared to the practicums that were carried out virtually. The reason for direct practicum is more effective and efficient, dominantly stated by the respondents. This can be attributed to the most common obstacle found when practicing practicum using a virtual lab is the difficulty of the teacher in explaining and increasing student focus. Even though from their preference level they prefer and are comfortable with practicums that are carried out directly, but they are also more concerned with the safety and sustainability of the practicums. More than 90% of respondents chose the need to implement virtual practicum during the pandemic. It can be concluded that the teachers consider that practical learning still needs to be carried out despite the pandemic conditions. In a pandemic condition, practical learning can still be done using a virtual lab application.